Encyclopaedia of religion and ethics ; v. 10 - Hastings, James; Selbie, John A.; Gray, Louis H. (Edinburgh, Scotland T and T Clark, 1915)
Contents : v. 10 : Picts - Sacraments
Keywords: Religion -- encyclopaedias; Ethics -- encyclopaedias